2014
DOI: 10.7554/elife.05352
|View full text |Cite
|
Sign up to set email alerts
|

Corticothalamic phase synchrony and cross-frequency coupling predict human memory formation

Abstract: The anterior thalamic nucleus (ATN) is thought to play an important role in a brain network involving the hippocampus and neocortex, which enables human memories to be formed. However, its small size and location deep within the brain have impeded direct investigation in humans with non-invasive techniques. Here we provide direct evidence for a functional role for the ATN in memory formation from rare simultaneous human intrathalamic and scalp electroencephalogram (EEG) recordings from eight volunteering patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 77 publications
8
85
0
Order By: Relevance
“…Thus, a possible mechanism of DBS is to induce enhanced high frequency neural activity of the basal ganglia-thalamocortical network to disrupt abnormal excessive coupling (95) and regularize neuronal firing (96), a phenomenon that has been called an “informational lesion”(97). We should also note that there is emerging evidence of the involvement of thalamic structures in control of cortical oscillations in both attention via the pulvinar (98) and memory via the anterior thalamic nucleus (45). These findings suggest that thalamic modulation might provide a venue for treatment of deficits outside the motor domain.…”
Section: Neural Communication Pathologymentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, a possible mechanism of DBS is to induce enhanced high frequency neural activity of the basal ganglia-thalamocortical network to disrupt abnormal excessive coupling (95) and regularize neuronal firing (96), a phenomenon that has been called an “informational lesion”(97). We should also note that there is emerging evidence of the involvement of thalamic structures in control of cortical oscillations in both attention via the pulvinar (98) and memory via the anterior thalamic nucleus (45). These findings suggest that thalamic modulation might provide a venue for treatment of deficits outside the motor domain.…”
Section: Neural Communication Pathologymentioning
confidence: 98%
“…We propose that PAC provides a bridge between local microscale (36; 37) and systems-level macroscale neuronal ensembles (29; 31; 38; 39) allowing for dynamic network communication (4043). This assertion is supported by the fact that PAC tracks behavior, including learning (44; 45), working memory performance (46), attention (47), and reward processing (48; 49), across species (50) (see Johnson and Knight, 2015 (51) for a review). Recent evidence suggests that PAC might operate over short (< 500 ms) timescales, providing a mechanism for interregional coordination between the oscillatory local field and broadband gamma (52).…”
Section: Oscillatory Communicationmentioning
confidence: 99%
“…For example, a recent intracranial study in humans investigated the role of phase synchrony between frontal areas and the anterior thalamic nucleus (ATN) for memory formation (Figure 2A, [49]). The authors found increased PFC-ATN phase-locking in the theta-band (4-8 Hz) for successfully encoded items.…”
Section: Large-scale Network Dependent On Prefrontal Cortexmentioning
confidence: 99%
“…Coupling between gamma activity and the phase of theta or alpha oscillations has been reported in several MEG studies8910, and in invasive recordings from humans and non-human primates4111213141516171819. The CFC has been proposed to play a fundamental role for organizing neuronal processing in space and time362021.…”
mentioning
confidence: 92%